Chemical composition and insecticidal activity of the essential oil from Helichrysum faradifani endemic to Madagascar. Issue 14 (18th July 2018) - Benelli, Giovanni; Pavela, Roman; Rakotosaona, Rianasoambolanoro; Randrianarivo, Emmanuel; Nicoletti, Marcello; Maggi, Filippo
Abstract: Helichrysum faradifani (Asteraceae) is a perennial shrub growing in rocky and sandy places of Madagascar. The plant is used in the Malagasy traditional medicine as a wound-healing agent, disinfectant and for the treatment of syphilis, diarrhea, cough and headache. In the present work, we analysed the chemical composition of the essential oil distilled from the aerial parts of H. faradifani by GC-MS and evaluated its insecticidal activity against 2nd, 3rd and 4th instar larvae of the lymphatic filariasis vector Culex quinquefasciatus by acute toxicity assays. The most sensitive were 2nd instar (LC50 = 85.7 μL L −1 ) larvae. For the 3rd and 4th instar larvae, the estimated LC50 were 156.8 and 134.1 μL L −1, respectively. Monoterpene hydrocarbons (51.6%) were the major fraction of the essential oil, with the bicyclic α-fenchene (35.6%) as the predominant component. Sesquiterpene hydrocarbons (34.0%) were the second major group characterising the oil, with γ-curcumene (17.7%) as the most abundant component. Abstract :